Social media, Memes and Digital Emotional Contagion: Critical Thinking and Emotional Intelligence for Digital Citizenship Education - Sara Tabatabaei; Bulgarova Bella Akhmedovna; Trofimova Galina Nikolayevna; Barabash Victor Vladimirovich (مجلة النور للدراسات الانسانية)
This research objective is to investigate the impact of emerging technology, mediated by emotional contagion, on the formation of civic engagement to develop a new conceptual framework for digital citizenship education that promotes critical thinking and emotional intelligence skills.